Signal mining of botulinum toxin type A adverse events based on FAERS database and its implications for the treatment of cerebral palsy - Wang, Huajie; Ma, Shiyu; Lai, Jun; Huang, Yubin (Frontiers in Human Neuroscience, 2025)
ObjectiveBased on the US Food and Drug Administration Adverse Event Reporting System (FAERS), signal mining of adverse drug events (AEs) caused by Botulinum Toxin Type A (BoNTA) was performed to explore its safety implications for the treatment of cerebral palsy (CP).MethodsThe OpenVigil 2.1 platform was used to extract AE reports on BoNTA from the FAERS database, covering the period from the fourth quarter of 2003 to the second quarter of 2024. Safety data were analyzed using the Reporting Odds Ratio (ROR) and Proportional Reporting Ratio (PRR), with BoNTA designated as the primary suspect drug.ResultsA total of 124,538 AE reports related to BoNTA were identified, showing an overall upward trend in the annual report counts. Most reports originated from the United States, with patients predominantly aged 36–60 years and predominantly female. Prolonged hospitalization was the most frequently reported serious adverse event. Signal analysis identified 325 disproportionately reported events across 21 system-organ classes (SOCs). The top five preferred terms (PTs) by frequency were eyelid ptosis, dysphagia, muscle weakness, blurred vision, and injection site swelling. The top five PTs based on signal strength were brow ptosis, Mephisto sign, botulism, bizarre personal appearance, and neuromuscular toxicity. Notable lowest-level terms (LLTs) included eye swelling, injection site edema, facial pain, facial discomfort, increased residual urine volume, blurred vision, and eyelid swelling.ConclusionIn clinical practice involving BoNTA for CP treatment, clinicians should pay close attention to these identified signals. Strengthened pre-injection evaluation and post-injection monitoring are recommended to enable early detection and timely intervention, ensuring medication safety for patients.